Sejarah Penulisan Mushaf Al-Qur’an Nusantara: Kajian Perbandingan Antara Mushaf Istiqlal Indonesia Dengan Mushaf Malaysia - Makmur Haji Harun (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2016)
The history of a script the archipelago Mushaf is the starting point of art ornament mushaf development that is often the main sketches in the holy Qur'an. Implementation of writing and ornament was more beautiful when it was featured in the Istiqlal Indonesia and Malaysia mushaf. The existence of script and ornament was complemented the clear, bright, beautiful, unique and compelling on both the archipelago mushaf. Disclosure of this mushaf publishing history became important principles of the standard holy Qur’an in Indonesia and Malaysia to be read by the Islamic community. The development of these mushaf in Indonesia and Malaysia continued to be developed even continued to be refined using certain methods. In addition, it was also signaled the grandeur of various other artworks. Meanwhile, both the Mushaf had been proud for Muslims in the archipelago which was an artistic depiction of calligrapher expert hands. The methodology of this study used a comparative study with the deepening through the history of Indonesia and Malaysia mushaf. The objective of this study to see the unique script of archipelago mushaf that is often the basic symbols of art ornament and aesthetic quality in the Islamic community. The research findings are expected to develop a discourse of science to uncover the history and heritage of art and culture of Islam in the archipelago where the study was conducted.